BENTUK DAN FUNGSI RAGAM HIAS CANDI BUMIAYU III KABUPATEN MUARAENIM - Mainur Mainur (UNIVERSITAS INDO GLOBAL MANDIRI, 2018)
This article is about the form and function of Bumiayu III temple located in Muaraenim regency of South Sumatera Province. This study aims to develop and provide insight and information to the general public both artists, culturalists, art lovers, lovers of local culture and culture of the archipelago, who should know about the form and function of Bumiayu III temple.In cultural studies of the archipelago, the study of the existence of Bumiayu III temple is rare in South Sumatra.Therefore, the existence of decoration in the temple of Bumiayu III here is described briefly and presented qualitatively interactively with the Aesthetic Nusantara approach.Research method that is various relevant data can be used in supporting the continuity of research.Data collection starts from the study of observation, documentation, interview and literature study. From result of analysis to form and function of decoration of Bumiayu III temple ie; The explanation of the background of Bumiayu III temple, the purpose, the origin of the history of the temple Bumiayu III, continued the exposition of the function of the temple ornament consists of personal functions, social functions, and physical functions, in addition described also about the form of temple decoration ; motifs of plants (flora), animal motifs (fauna), and human motives (figures of deity) at Bumiayu III temple located in Muaraenim regency of South Sumatra Province.Keywords: shape, function of decoration of temple Bumiayu III